1990
DOI: 10.1002/app.1990.070391117
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR studies on water in methacrylate hydrogels. I

Abstract: SynopsisThe behavior of water contained in a hydrophilic hydrogel poly(hydroxyethy1 methacrylate) membrane and a hydrophobic hydrogel poly(methy1 methacrylate) membrane was studied by proton nuclear magnetic resonance (NMR) spectroscopy. Significant differences between the two hydrogels were observed in their relaxation times, the temperature dependence, and frequency dependence of these relaxation times, and changes of signal intensity of water protons on freezing and thawing. The water in these hydrogels was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…Therefore, the T 2 measurements of acidic solvent protons presented in Fig. 3 have been interpreted, like in other polysaccharides gels [21][22][23][24][25], in terms of a fast exchange which takes place between the free and bound state of water. However, in order to explain the reduction in the relaxation time observed for neutral and especially for acidic solvents, we have to assume that in addition to the fast exchange of water molecules, other mechanisms of the relaxation take place.…”
Section: Resultssupporting
confidence: 64%
“…Therefore, the T 2 measurements of acidic solvent protons presented in Fig. 3 have been interpreted, like in other polysaccharides gels [21][22][23][24][25], in terms of a fast exchange which takes place between the free and bound state of water. However, in order to explain the reduction in the relaxation time observed for neutral and especially for acidic solvents, we have to assume that in addition to the fast exchange of water molecules, other mechanisms of the relaxation take place.…”
Section: Resultssupporting
confidence: 64%
“…[13] Tightly bound (non-freezing) water has a NMR correlation time (t c ) value of 10 À8 -10 À6 s and does not crystallize even at À100 8C. [12,13] Loosely bound (intermediate) water has a t c value of 10 À10 -10 À9 s and exhibits melting/crystallization at temperatures below 0 8C. [12,13] Free water has t c value of 10 À12 -10 À11 s and crystallizes at 0 8C.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Loosely bound (intermediate) water has a t c value of 10 À10 -10 À9 s and exhibits melting/crystallization at temperatures below 0 8C. [12,13] Free water has t c value of 10 À12 -10 À11 s and crystallizes at 0 8C. [12,13] In addition, we have reported that the intermediate water is formed in a wide variety of biopolymers including proteins (albumin and gelatin), [14,15] polysaccharides (hyaluronan and chondroitin sulfate) and nucleic acids (DNA and RNA).…”
Section: Introductionmentioning
confidence: 99%
“…9 The water in hydrogels can be generally classified into three species: free water, freezing bound water, and nonfreezing bound water. Nonfreezing bound water, linking with hydrophilic group of the polymer network by hydrogen bond, does not freeze even at extra low temperature.…”
Section: Rheology Of Gpna Hydrogelsmentioning
confidence: 99%
“…It is difficult to distinguish the melting peaks of freezing bound water and free water, so they are calculated together. 9 The water states in GPNA hydrogels were studied by DSC.…”
Section: Rheology Of Gpna Hydrogelsmentioning
confidence: 99%